PENGARUH LITERASI KEUANGAN, KEMAMPUAN AKADEMIS, DAN PENGALAMAN BEKERJA TERHADAP PERILAKU KEUANGAN MAHASISWA - Pandu Adi Cakranegara; Mike Fetesond (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of Academic Ability, Financial Literacy, and Work Experience on Student Financial Behavior. This research was conducted using quantitative methods using a questionnaire as a research instrument to collect data. The sample in this study was the University of President Regular Malam 2018 students totaling 100 respondents with a purposive sampling method. The analysis technique used is multiple linear regression analysis and hypothesis testing with partial T-test and simultaneous F test. The results showed that the variables of Financial Literacy, Academic Ability, and Work Experience simultaneously had a significant influence on Student Financial Behavior. The results also show that Financial Literacy and Work Experience variables have a significant impact on Student Financial Behavior. Meanwhile, the Academic Ability variable has no significant impact on Student Financial Behavior. With an Adjusted R square value of 0.375, it means that 37.5% of Student Financial Behavior can be explained by the variables of Academic Ability, Financial Literacy, and Work Experience. While the remaining 62.5% can be explained by other reasons or influenced by other variables not included in the study.